Rangeland Suitability Evaluation for Livestock Production using Remote Sensing and GIS Techniques in Dire District, Southern Ethiopia (Global Journal of Science Frontier Research, 2015)
Management of complex ecosystems such as rangelands needs adequate knowledge to consider its capability for sustainable utilization. Land suitability analysis is needed to make proper land-use planning. GIS and Remote Sensing techniques offer a convenient and powerful platform to integrate spatially complex and different land attributes for performing land suitability analysis. The present study was intended to analyze and map suitable areas for livestock production in Dire district using remote sensing and GIS techniques. The study made use of Landsat TM 2011 remote sensing satellite image for land-use/land-cover analysis, and Multi Criteria Evaluation in a GIS environment to come up with the final suitability map.
Keywords: GIS; livestock; multi criteria evaluation; rangeland; remote sensing; suitability analysis